Schistura maculosa, a new species of loach (Teleostei: Nemacheilidae) from Mizoram, northeastern India - Lalronunga, Samuel; Lalnuntluanga, Lalnuntluanga; Lalramliana, Lalramliana (Zootaxa, 2013)
Schistura maculosa, a new species of loach, is described from Tuingo and Pharsih Rivers, tributaries of Tuivai River (Barak drainage) in Mizoram, northeastern India. It is distinguished from other closely related Schistura species in having an axillary pelvic lobe; an incomplete lateral line; 20–30 narrow black bars on the body; 3–4 rows of black spots horizontally across the dorsal-fin; a slightly emarginate caudal-fin, with 5–7 rows of black spots more or less regularly arranged vertically on rays across the fin, and 8+8 branched caudal-fin rays.